Association of angiotensin-converting enzyme gene polymorphism with pulse pressure and its interaction with obesity status in Heilongjiang province. (2nd January 2019) - Wang, Ningning; Li, Xueyan; Zhang, Qi; Zhang, Hao; Zhou, Li; Wu, Nan; Jin, Ming; Qiu, Changchun; Zhang, Keyong
ABSTRACT: Angiotensin I converting enzyme ( ACE ) gene is one of the most-studied candidate genes related to essential hypertension (EH). Pulse pressure (PP) may reflect vascular stiffness, especially in patients with EH, and has been used to predict EH. Previous evidence has indicated that obesity is a traditional risk factor of hypertension. The aim of the present study was to investigate the interaction between the obesity status and ACE gene polymorphisms on the development of high level of PP. A total of 1980 adults (1024 hypertensive and 956 normotensive) were included in this study and genotyped for ACE gene polymorphisms. The results showed that rs4343 and rs4351 in ACE gene were risk factors of high level of pulse pressure (p < 0.05). We also detected positive interactions between the two SNPs and obesity status in the pathway of high level PP.